(3eHGOF GdeYGOdGJ GdJaGVdjI (B/s - (3GHQGgje, eYf YHO GdeLjOs ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ h GdJhRjY(B, s, 2007)
(3gPG GdcJGH jeJGR HCSdhHg GdfXQj GdoeHnSW hGdoehLR MjK jJfGhd CMO YTQ aUdkG JZWj ehGVjY GdoeYGOdGJ GdJaGVdqjI, jYQoV GdaUd GdChd JYGQja heaGgje CSGSjI heSGFd ChdqjI dMd GdoeYGOdI GdJaGVdqjI, hjZWj GdaUd GdKGfj GdoeYGOdGJ GdJaGVdqjI ef GdeQJHI GdChdi, hjJfGhd WQjbI aUd GdeJZjQGJ hGdoeYGOdI GdeJLGfSI hGdoeYGOdI GdJGeI, hoNUU GdaUd GdKGdK dOQGSI GdoeYGOdGJ GdJaGVdqjI GdNWqjI, hGdJYqQa Ydi eMOOI aQhfScjGf deYQaI GdESJbdGd GdNqWj ddOhGd, aVdkG Yf GdJYQa Ydi GdeDKQGJ GdJaGVdqjI hNhGUgG(B. (3jJfGhd GdaUd GdQGHY GdoeYGOdGJ GdJaGVdqjI PGoJ GdoeYGedGJ GdKGHJI, hbO GSJNOe YOI WQb dEjLGO GdMd GdYGe ddoeYGOdI GdeJLGfSI hZjQ GdeJLGfSI, CeG GdaUd GdNGeS abO oNUU dEjLGO GdMd GdNGU ddoeYGOdGJ ZjQ GdeJLGfSI HESJNOGe WQjbI GdoeYGedGJ ZjQ GdeMOOI, GdaUd GdSGOS(B: (3JfGhd ajg OQGSI WQjbJjf ZjQ eQJHWJjf HCj bjhO aj Md GdoeYGOdGJ GdNWqjI PGJ GdoeYGedGJ GdeJZjQI geG(B: (3WQjbI ENJRGd GdQJHI hWQjbI JZGjQ GdHGQGeJQGJ(B. (3hGdaUd GdSGHY OQS JWHjbGJ ddoeYGOdGJ GdJaGVdqjI GdNWqjI GdJj JMJhj Ydi GdEgJRGRGJ GdejcGfjcqjI, GdaUd GdKGef oNUU dMd GdoeYGOdGJ GdJaGVdqjI GdLRFjI ef GdeQJHI GdChdi hGdKGfjI, hSdWfG GdVhA Ydi GdoeYGOdGJ GdRGFOqjI, GdecGaFqjI, GdJfGbUqjI, Md OjdeHQJ doeYGOdI GdehLI, eSGFd GdbjeI GdEHJOGFjI heSGFd GdbjeI GdnMqOjI, WQjbI aUd GdoeJZjQGJ, hbO hXaJ GdaUhd(B: (3GdJGSY hGdYGTQ hGdMGOj YTQ dOQGSI OhGd ncGeG, HjSjd, YOjO MOhO djLjfOQ, hJMhjd dGHdGS, hoeJSdSdI ahQjjQ(B.s
(3HjHdjhZQGajG U(B.491s
Keywords: (3GdJaGVd hGdJcGeds; (3QjGVjGJs; (3eYGOdGJ JaGVjdIs